Structural and functional improvement of amygdala sub-regions in postpartum depression after acupuncture - Huang, Xingxian; Zhuo, Yuanyuan; Wang, Xinru; Xu, Jinping; Yang, Zhuoxin; Zhou, Yumei; Lv, Hanqing; Ma, Xiaoming; Yan, Bin; Zhao, Hong; Yu, Haibo (Frontiers in Human Neuroscience, 2023)
To analyze the changes of structure and function in amygdala sub-regions in patients with postpartum depression (PPD) before and after acupuncture. A total of 52 patients with PPD (All-PPD group) were included in this trial, 22of which completed 8 weeks of acupuncture treatment (Acu-PPD group). An age-matched control group of 24 healthy postpartum women (HPW) from the hospital and community were also included. Results from the 17- HAMD and the EPDS were evaluated and rs-fMRI scans were performed at baseline and after the acupuncture treatment. Sub-regions of the amygdala were used as seed regions to measure GMV and analyzed for RSFC values separately. Finally, Correlation analyses were performed on all patients with PPD to evaluate association values between the clinical scale scores, GMV, and RSFC values, while controlling for age and education. Pearson correlation analyses were conducted to investigate the relevance between GMV, RSFC values of brain regions that differed before and after acupuncture treatment and clinical scale scores in Acu-PPD patients. The HAMD scores for Acu-PPD was reduced after acupuncture treatment (P < 0.05), suggesting positive effects of acupuncture on depression symptoms. Structurally, All-PPD group showed significantly decreased GMV in the left lateral part of the amygdala (lAMG.L) and the right lateral part of the amygdala (lAMG.R) compared to the HPW group. In addition, the GMV of lAMG.R was marginally increased in the Acu-PPD group after acupuncture .Functionally, the Acu-PPD group showed a significantly enhanced RSFC between the left medial part of the amygdala (mAMG.L) and the left vermis_6, an increased RSFC between the right medial part of the amygdala (mAMG.R) and left vermis_6, and an increased RSFC between the lAMG.R and left cerebelum_crus1. Moreover, correlation studies revealed that the GMV in the lAMG.R was significantly related to the EPDS scores that in the All-PPD group. Our findings demonstrated that the structure of amygdala sub-regions is impaired in patients with PPD. Acupuncture may improve depressive symptoms in patients with PPD, and the mechanism may be attributed to changes in the amygdala sub-region structure and the functional connections of brain areas linked to the processing of negative emotions.